2015
DOI: 10.1021/acs.joc.5b01178
|View full text |Cite
|
Sign up to set email alerts
|

Amide Oxygen-Assisted Palladium-Catalyzed Hydration of Alkynes

Abstract: Herein, an amide oxygen-assisted palladium-catalyzed hydration reaction of alkynes is realized to prepare a series of o-acylacetanilide derivatives with high yield, and single regioselectivity under mild reaction conditions. This transformation is simple, practical, and can be performed on a gram scale. Evaluation of the mechanism shows that the reaction should involve an oxypalladation process, and the 1,3-oxazine compound is proven to be a key intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 67 publications
0
20
0
1
Order By: Relevance
“…In 2015, Jiang et al [22] developed the first Pd-catalyzed intramolecular amide oxygen-bond participation in hydration of alkynes 38 to prepare o-acylacetanilide derivatives 39 through an oxypalladation process with exclusive regioselectivity (Scheme 11). The selectivity could be rationalized through the intermediacy of a Pdbound 1,3-oxazine species 38A obtained after 6-exodig cyclization of amide oxygen to the Pd-coordinated alkyne.…”
Section: Amide's Oxygen Assistance In Palladium-catalyzed Hydrationmentioning
confidence: 99%
“…In 2015, Jiang et al [22] developed the first Pd-catalyzed intramolecular amide oxygen-bond participation in hydration of alkynes 38 to prepare o-acylacetanilide derivatives 39 through an oxypalladation process with exclusive regioselectivity (Scheme 11). The selectivity could be rationalized through the intermediacy of a Pdbound 1,3-oxazine species 38A obtained after 6-exodig cyclization of amide oxygen to the Pd-coordinated alkyne.…”
Section: Amide's Oxygen Assistance In Palladium-catalyzed Hydrationmentioning
confidence: 99%
“…What is more, the amide motif has also served as pivotal intermediate to generate several other organic functionalities [89]. To date, a large number of amidation reactions have been established [1011], such as the condensation of carboxylic acid derivatives with amines [12], the rearrangement of ketoximes [13], the C–N cross coupling between aromatic amides or amines and aryl(pseudo)halides [1415] or aldehydes [1620]. However, to the best of our knowledge, the studies of dehydrogenative cross-oxidative-coupling reactions between methylarenes and amines for the formation of amides are rather limited, and which would be an important complement to the conventional C–N forming strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the reactivity of some ortho functional group of acetanilides is modulated by the presence of the N-acetyl moiety, which is thus selectively converted to more complex compound, constituting this kind of acetanilide into important synthetic intermediates. 5,[9][10][11][12][13] Due to the abovementioned applications, new developments in the acetylation procedure are still desirables, and representative contributions are described, Figure 2. [14][15][16][17][18][19][20][21][22][23][24] Furthermore, in undergraduate courses, the parent acetanilide is extensively synthesized as classical preparation of aromatic amide.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, a search in the literature revealed that when other substituted acetanilides are needed as starting material in the context of a research project, the preparation used is very similar to that of parent acentanilide, which is almost the same of one century ago, which uses large amounts of solvents and additives such as acetic acid and sodium acetate, for instance. [5][6][7][8][9][10][11][12][13][14][15][19][20][21][22][23][24] It should be pointed out that, although there are a few syntheses of acetanilides in the absence of solvent, it is always necessary the use of grinding or microwave heating in these previously described syntheses or, more recurrent, the use of catalyst such as morpholinium bisulfate, zirconyl triflate, tris(pentaflurophenyl)borate, anatase phase TiO 2 nanoparticles, or even the unconventional rice husk ash, Figure 2. 24 Despite that solvent-free catalyst's dependent approaches represent important contribution, more environmentally friendly procedures which reduce the use of chemicals and energy is still needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation